Sodium bicarbonate as a blowing agent on morphology and properties of conductive carbon black-filled epoxy porous prepared by emulsion system - Anusha Leemsuthep, Am Phan (Universiti Malaysia Perlis (UniMAP), 2017)
Master of Science in Materials Engineering